Comparison of resistance and concurrent resistance and endurance training regimes in the development of strength - Shaw, B. S.; Shaw, I.; Brown, G. A. (The Journal of Strength and Conditioning Research, 2009)
Resistance and endurance training are often performed concurrently in most exercise programs and in rehabilitative settings in an attempt to acquire gains in more than 1 physiologic system. However, it has been proposed that by simultaneously performing these 2 modes of exercise training, the strength gains achieved by resistance training alone may be impaired. Thus, the aim of this study was to compare the effects of 16 weeks of resistance training and concurrent resistance and endurance training on muscular strength development in 38 sedentary, apparently healthy males (25 yr ± 8 mo). Subjects were age-matched and randomly assigned to either a control (Con) group (n = 12), resistance training (Res) group (n = 13), or concurrent resistance and endurance training (Com) group (n = 13). After 16 weeks, no changes were found in the strength of the subjects in the Con group. Resistance training and concurrent resistance and endurance training significantly (p < 0.05) improved strength in all of the 8 prescribed exercises. The data also indicated that 16 weeks of concurrent resistance training and endurance training was as effective in eliciting improvements in strength as resistance training alone in previously sedentary males. As such, concurrent resistance and endurance training does not impede muscular strength gains and can be prescribed simultaneously for the development of strength in sedentary, apparently healthy males and thus may invoke all the physiologic adaptations of resistance and endurance training at once.